Meningkatkan Partisipasi Mahasiswa pada Program MBKM Mandiri-Asistensi Mengajar melalui Pelatihan Mandiri Terintegrasi - Herianto, Edy; Haslan, M. Mabrur; Ainun, Ainun; Septiana, Elyn; Aziz, Sahril; Suryani, Ade Irma; Sahira, Emilia; Novitasari, Novitasari (Universitas Mataram, 2024)
Integrated Independent Training aims to increase the participation of students, supervising lecturers, and mentor teachers in MBKM, especially the Independent-Teaching Assistance (MBKM Mandiri-AM) activity at the FKIP, University of Mataram. This program includes preparation, implementation, evaluation, and follow-up to support teaching and mentoring. The results are (1) MBKM effectively supports IKU achievements through direct experience-based activities, such as AM-Mandiri and Kampus Mengajar, compared to independent study and (2) Integrated Independent Training improves the understanding of Supervising Lecturers, Mentor Teachers, and Students. Follow-up after the training includes semester preparation, information dissemination, and reinforcement through support, monitoring, and follow-up programs. Recommendations for development in the form of program expansion are suggested through social media, public lectures, and training. From this entire process, it can be concluded that this program has great potential to increase the involvement and quality of MBKM implementation at the FKIP, University of Mataram